Red-Shift (2-Hydroxyphenyl)-Benzothiazole Emission by Mimicking the Excited-State Intramolecular Proton Transfer Effect - Ren, Yong; Zhou, Lei; Li, Xin (Frontiers in Chemistry, 2021)
Novel strategies to optimize the photophysical properties of organic fluorophores are of great significance to the design of imaging probes to interrogate biology. While the 2-(2-hydroxyphenyl)-benzothiazole (HBT) fluorophore has attracted considerable attention in the field of fluorescence imaging, its short emission in the blue region and low quantum yield restrict its wide application. Herein, by mimicking the excited-state intramolecular proton transfer (ESIPT) effect, we designed a series of 2-(2-hydroxyphenyl)-benzothiazole (HBT) derivatives by complexing the heteroatoms therein with a boron atom to enhance the chance of the tautomerized keto-like resonance form. This strategy significantly red-shifted the emission wavelengths of HBT, greatly enhanced its quantum yields, and caused little effect on molecular size. Typically, compounds 12B and 13B were observed to emit in the near-infrared region, representing the smallest organic structures with emission above 650 nm.